Abnormal aortic flow conduction is associated with increased viscous energy loss in patients with repaired tetralogy of Fallot. (18th September 2019) - Schäfer, Michal; Barker, Alex J; Jaggers, James; Morgan, Gareth J; Stone, Matthew L; Truong, Uyen; Browne, Lorna P; Malone, Ladonna; Ivy, D Dunbar; Mitchell, Max B
Abstract: : OBJECTIVES: Aortopathy in tetralogy of Fallot (TOF) is characterized by increased aortic stiffness, dilation and reduced left ventricular (LV) function. Repair in infancy normalizes aortic dimensions in early childhood. Our prior work demonstrated that early TOF repair does not normalize aortic compliance and that abnormal ascending aortic flow patterns are prevalent. The objectives of this study were to: (i) determine whether proximal aortic flow-mediated viscous energy loss (E L ′ ) is elevated in patients with early TOF repair compared with healthy controls, and (ii) determine whether the degree of E L ′ is associated with LV function. METHODS: Forty-one patients post TOF repair with normalized aortic size and 15 healthy controls underwent 4-dimenisonal-flow magnetic resonance imaging flow analysis and E L ′ assessment. Correlations between E L ′, aortic size, and LV function were assessed. RESULTS: The TOF group had increased peak systolic thoracic aorta E L ′ (3.8 vs 1.5 mW, P = 0.004) and increased averaged E L ′ throughout the cardiac cycle (1.2 vs 0.5 mW, P = 0.003). Peak and mean systolic E L ′ in the ascending aorta was increased 2-fold in the TOF group compared with control (peak: 2.0 vs 0.9 mW, P = 0.007). Peak E L ′ measured along the entire thoracic aortic length correlated with LV ejection fraction ( R = −0.45, P = 0.009), indexed LV end-systolic volume ( R = −0.40, P = 0.010), and right ventricular end-systolic volume ( R = −0.37, P = 0.034). CONCLUSIONS: Patients with repaired TOF exhibit abnormal aortic flow associated with increased E L ′ in the thoracic aorta. The magnitude of E L ′ is associated with LV function and volumes. Increased aortic E L ′ in TOF is likely due to inherently abnormal LV outflow geometry and or right ventricular interaction. Reduced aortic flow efficiency in TOF increases cardiac work and may be an important factor in long-term cardiac performance.